Seasonal changes in trophic ecology of co-occurring freshwater invasive species at a thermal locality - Balzani, Paride; Musil, Martin; Weiperth, András; Bláha, Martin; Kubec, Jan; Ruokonen, Timo J.; Ercoli, Fabio; Bányai, Zsombor M.; Buřič, Miloš; Veselý, Lukáš; Kouba, Antonín (Springer Science and Business Media LLC, 2025)
We investigated the trophic ecology of three non-native crayfish species (the marbled crayfish Procambarus virginalis, the red swamp crayfish Procambarus clarkii and the spiny-cheek crayfish Faxonius limosus) and two non-native fishes (the eastern mosquitofish Gambusia holbrooki and the three-spined stickleback Gasterosteus aculeatus) from two sections of a thermal tributary of the Barát brook in Budapest (Hungary) over the four seasons using carbon and nitrogen stable isotope analysis. All crayfish species occupied an omnivore trophic position in almost all sections and seasons. On the other hand, both fishes had a predatory trophic position, with G. aculeatus occupying a higher position than G. holbrooki. These patterns are confirmed by the results of the mixing models, showing spatial and temporal changes in the diet composition. We also found interspecific differences in the crayfish trophic niche in both sections during summer and overlapped niches in the other occasions, while fish had always segregated niches. Crayfish showed interseasonal differences in the trophic niche in both sections, while fish showed seasonal niche shifts only in the upper section. Our results show a considerable plasticity in the trophic ecology of the studied non-native populations, suggesting that the temperature variability gradient has no important role in determining their trophic niche.
Keywords: alien species; invasive species; stable isotopes; freshwater ecology; competition; predation